Haploid induction: an overview of parental factor manipulation during seed formation - Song, Jingpu; Datla, Raju; Zou, Jitao; Xiang, Daoquan (Frontiers in Plant Science, 2024)
In plants, in vivo haploid induction has gained increasing attention for its significant potential applications in crop breeding and genetic research. This strategy reduces the chromosome number in progeny after fertilization, enabling the rapid production of homozygous plants through double haploidization, contrasting with traditional inbreeding over successive generations. Haploidy typically initiates at the onset of seed development, with several key genes identified as paternal or maternal factors that play critical roles during meiosis, fertilization, gamete communication, and chromosome integrity maintenance. The insights gained have led to the development of efficient haploid inducer lines. However, the molecular and genetic mechanisms underlying these factors vary considerably, making it challenging to create broadly applicable haploidy induction systems for plants. In this minireview, we summarize recent discoveries and advances in paternal and maternal haploid induction factors, examining their current understanding and functionalities to further develop efficient haploid inducer systems through the application of parental factor manipulation.